Development and Standardization of a High-Throughput Bordetella pertussis Growth-Inhibition Assay - Thiriard, Anaïs; Raze, Dominique; Locht, Camille (Frontiers in Microbiology, 2020)
Bordetella pertussis, the main causative agent of whooping cough, is a reemerging pathogen, and recent vaccine-resistant strain outbreaks and emergence of macrolides-resistant strains in China raised new concerns for control of the disease. New vaccines and potentially new antibiotics are thus needed. B. pertussis is tedious to culture and requires several days of growth to count isolated colonies on agar-based media, making large-scale screening of new anti-B. pertussis compounds or functional evaluation of large sample sizes of immune sera difficult. Here, we developed a scalable, rapid, high-throughput luminescence-based Bordetella growth inhibition assay (BGIA) to quantify surviving bacteria after treatment with anti-B. pertussis compounds. A strong correlation between luminescence and colony-forming unites (r²=0.9345, p< 0.0001) was found and the BGIA showed high sensitivity and reproducibility. We demonstrate here that the BGIA can be used to quantify resistance of B. pertussis to antibiotics, sensitivity to complement and to human serum in an easy-to-operate and fast manner. We have optimized the assay and assessed the effects of differences between B. pertussis strains and growth conditions on serum and complement sensitivity and uncovered complement-independent antibody-mediated inhibition of B. pertussis growth. The BGIA can thus effectively be implemented for large-scale serum studies to deeper investigate anti-B. pertussis immune responses at a functional level, as well as for screening of B. pertussis strains for their resistance to antibiotics or complement, and for high-throughput screening of novel anti-B. pertussis compounds.